Combining experiential and social learning approaches for crop disease management in a smallholder context: a complex socio-ecological problem - Tafesse, S.; Mierlo, B. van; Leeuwis, Cees; Lie, R.; Lemaga, B.; Struik, P.C. (Springer, 2020)
Effective management of crop diseases is a key precondition for sustainable crop production and to improve food security globally. However, learning approaches that improve smallholder farmers’ knowledge, perceptions, and practices to deal with crop diseases by fostering social and technical innovations are seldom studied. A study was conducted to examine: (1) how a combination of experiential and social learning approaches influences potato farmers’ knowledge, perceptions, and practices in bacterial wilt and its management in Ethiopia and (2) the implications of combining the two approaches for complex crop disease management in smallholder context. Data were derived from face-to-face in-depth interviews, reflective workshops, and participant observations. The findings showed that farmers’ knowledge and perceptions about disease incidence, the pathogen that causes the disease, its spreading mechanisms, host plants, and disease diagnosis were changed. Farmers’ practices in management of the disease were also improved. Learning about the cause of the disease stimulated the identification of locally relevant spreading mechanisms and the feasibility of a range of recommended disease management methods. Moreover, farmers recognized their interdependency, role, and responsibility to cooperate to reduce the disease pressure in their community. We conclude that learning interventions aiming to improve smallholder farmers’ knowledge, perceptions, and practices to deal with complex crop diseases need to combine experiential and social learning approaches and consider farmers’ local knowledge.